What's trending in libraries from the internet cybersphere – artificial intelligence and other emerging technologies. Issue 2 (3rd April 2017) - Oyelude, Adetoun A.
Abstract : Purpose: The article is the first for this column for 2017. It is full of information mainly from blogs and wikis. The aim of the article is to highlight trends in technology in libraries as posted on the blogs and wikis. Design/methodology/approach: The methodology used is that of getting the most trending news from the wikis and blogs in the first quarter of the year and reporting on them. Findings: The projections for the year are emphasized moving from artificial intelligence to information literacy. Originality/value: These are the trends projected from the internet cybersphere. It sure is trending!